2002
DOI: 10.1038/modpathol.3880487
|View full text |Cite
|
Sign up to set email alerts
|

Loss of p53 and c-myc Overrepresentation in Stage T2-3N1-3M0 Prostate Cancer are Potential Markers for Cancer Progression

Abstract: To determine whether genetic changes are markers of cancer progression and patient survival in Stage T 2-3 N 1-3 M 0 prostatic carcinoma, we compared 26 patients who died of tumor relapse after prostatectomy and lymphadenectomy (case group) with 26 matched patients who were alive at the time of the matched case's death (control group). Nine unmatched cases were also included in this study. In 37 cases, paired primary tumors (119 foci) and lymph node metastases (114 foci) were available for study. Fluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 21 publications
4
39
1
1
Order By: Relevance
“…The oncogene c-Myc enhances protein translation through transactivating diverse targets, such as initiation factors, ribosomal proteins, and rRNAs. Activation of c-Myc is found in a variety of cancers, including breast cancer, and its activation seems to be a surrogate marker for cancers (44)(45)(46)(47)(48)(49). The role of c-Myc in driving protein synthesis is in part attributed to promoting ribosome production through transcribing a number of ribosomal proteins (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…The oncogene c-Myc enhances protein translation through transactivating diverse targets, such as initiation factors, ribosomal proteins, and rRNAs. Activation of c-Myc is found in a variety of cancers, including breast cancer, and its activation seems to be a surrogate marker for cancers (44)(45)(46)(47)(48)(49). The role of c-Myc in driving protein synthesis is in part attributed to promoting ribosome production through transcribing a number of ribosomal proteins (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Amplification of the c-myc locus 8q24 is linked to higher Gleason scores (Qian et al, 2002) and a poor prognosis (Sato et al, 1999;Tsuchiya et al, 2002). Concerning MYC protein expression, only two studies have been published for prostate cancer tissue so far.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, additional increases of c-myc (AI-c-myc) have been associated with a higher Gleason score and poorer survival in men with Stage pT 3 n 0 M 0 prostate cancer (reviewed in ref. 40). In a study based on histopathological examination of surgical specimens from a cohort of 52 patients, Qian et al demonstrated that AI-c-myc was strongly associated with high Gleason score, and thus with prostate cancer progression, and proposed c-myc as a potential marker of survival in Stage T (2)(3) n (1-3) M (0) prostate cancer (40).…”
Section: Chromosomal Alterations and Oncogene/tumor Suppressor Involvmentioning
confidence: 99%